Tasa de Éxito del Autotrasplante Dental de Terceros Molares. Revisión de la Literatura (2023)
Partial edentulism is the loss of one or more teeth, it can occur in young or elderly individuals and has various causes such as poor oral hygiene, dental caries, periodontal disease and sociodemographic level, where the treatment options for this diagnosis are fixed partial prosthesis, removable partial prosthesis and dental implants, however, dental autotransplantation is a good option in conservative dentistry. O